Pengaruh motivasi berprestasi dan lingkungan teman sebaya terhadap akhlakul karimah peserta didik - Annisa Ma'rifatul Jannah; Abd. Madjid (At Turots: Jurnal Pendidikan Islam, 2023)
The study aims at finding out the influence of achievement motivation and same-age friends’ environment on SMP Muhammadiyah 1 Gamping class VII students’ akhlakul karimah. The approach used in the study was quantitative. Moreover, the data collection methods used were questionnaires. The collected data were analyzed using quantitative data analysis with a multiple linear regression model. The result of the study shows that, from 110 respondents, achievement motivation possessed by the SMP Muhammadiyah 1 Gamping class VII students was very good, obtaining 96%. Furthermore, the environment variable of same-age friends indicated a very good same-age friends’ environment with a percentage of 99%. Meanwhile, for the Y variable of akhlakul karimah, 57% of the students have good akhlakul karimah. Moreover, from this study, the tcount value for the achievement motivation variable was 6,994 and the thirung value for the peer environment variabel was 4,811. Meanwhile, the table value for the sample is 110 respondents, which is 1,65882. If we conclude, 6,994 and 4,811 > 1,65884, there is a significant influence between the X variable partially towards the Y variable. Meanwhile, in calculating the influence simultaneously, it was revealed that F count > F table, 60.473 > 3.08. From the data, it could be concluded that there was a very significant influence between achievement motivation and same-age friends’ environment simultaneously towards SMP Muhammadiyah 1 Gamping class VII students’ akhlakul karimah, with a percentage of 53.2%.